(untitled) (Journal of Informatics Education and Research, 2025)
The age old issue of transforming strategic plans of high levels to practical operational outcomes has been an issue of big concern to the big businesses. This paper investigates the important, yet often undervalued, role of middle management or the most important factor in the solution to this strategy- execution gap. On an argument other than the traditional view of middle managers being an implementation body, this paper proposes the middle managers to be strategic decoders, communication and operational integrators. In this paper, a synthesis of the existing body of literature is performed to develop knowledge on the roles of middle management which are multifaceted, using a systematic literature review and theoretical analysis. The key conclusions are connected with the fact that their value becomes increasingly dependable on the opportunities to utilize digital tools, make decisions relying on data and make organizations more flexible. Core competencies, including strategic translation, resource orchestration, and change facilitation, are also identified to be of high significance to success in the analysis.